2015
DOI: 10.1136/bcr-2014-208855
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of fatal stroke after ethylene glycol toxicity

Abstract: SUMMARYA 58-year-old man presented to the emergency department with acute left-sided weakness and left visual field defect. His examination was significant for confusion, acetone odour, tachycardia and tachypnoea. Further blood tests revealed an anion gap of 31 mEq/L, serum osmolal gap of 34 mOsm/kg, and creatinine 3.6 mg/dL. Brain MRI revealed acute infarctions scattered throughout the brain along with generalised oedema. The patient deteriorated rapidly and soon thereafter it was reported that a bottle of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…Initial MRI scans were generally obtained within a few days of ingestion but some as late as 6 months after EG consumption. Similar to CT, abnormalities were typically seen in the basal ganglia, thalami, temporal lobe, and brainstem, 18,20,[24][25][26][27] with a few interesting exceptions. Lewis et al reported a patient with cranial nerve dysfunction, bilateral fifth cranial nerve inflammation, dilatation of the lateral ventricle temporal horns, and communicating hydrocephalus on an MRI obtained 11 days after EG ingestion.…”
Section: Discussion Clinical Progression Of Ethylene Glycol Toxicitymentioning
confidence: 86%
“…Initial MRI scans were generally obtained within a few days of ingestion but some as late as 6 months after EG consumption. Similar to CT, abnormalities were typically seen in the basal ganglia, thalami, temporal lobe, and brainstem, 18,20,[24][25][26][27] with a few interesting exceptions. Lewis et al reported a patient with cranial nerve dysfunction, bilateral fifth cranial nerve inflammation, dilatation of the lateral ventricle temporal horns, and communicating hydrocephalus on an MRI obtained 11 days after EG ingestion.…”
Section: Discussion Clinical Progression Of Ethylene Glycol Toxicitymentioning
confidence: 86%
“…Несостоятельность насосной функции сердца и поражение витальных центров ретикулярной формации на фоне острого токсического повреждения почек приводят к смертельному исходу. Таким образом, причиной смерти животных стало острое отрав ление ЭГ с развитием токсической энцефалопатии с поражением витальных центров и мозжечка, ОПП с дистрофическими и некробиотическими изменениями эпителия канальцев по типу тубулярного некроза, очаговым контрактурным поражением кардиомиоцитов, гидропической дистрофии гепатоцитов, что соотносилось с данными как экспериментов [22], так и клинических наблюдений за отравленными ЭГ пациентами [1,23].…”
Section: результаты и обсуждениеunclassified